The Importance of Conscientiousness to Audit Quality: Engagement Partner Graduate Thesis Typos and Audit Adjustments - He, Xianjie; Pittman, Jeffrey; Sun, Shuwei; Zhuang, Zili (The Accounting Review, 2026)
ABSTRACT Relying on the frequency of typos in engagement partners’ graduate theses to measure their conscientiousness, we find that more conscientious partners conduct higher-quality audits, evident in that they are more likely to require an audit adjustment. Our core results hold for both upward and downward adjustments, implying that being conscientious is not equivalent to being overly conservative. Consistent with DeAngelo’s (1981) theory, cross-sectional evidence suggests that the role that partner conscientiousness plays in audit quality comes through both the auditor competence and independence channels. Additionally, we find that the frequency of partner thesis typos is negatively associated with auditor effort. Collectively, our evidence implies that engagement partner conscientiousness plays a major role in shaping audit outcomes. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: M42.